Detrusor Smooth Muscle KV7 Channels: Emerging New Regulators of Urinary Bladder Function - Malysz, John; Petkov, Georgi V. (Frontiers in Physiology, 2020)
Relaxation and contraction of the urinary bladder smooth muscle, also known as the detrusor smooth muscle (DSM), facilitate the micturition cycle. DSM contractility depends on cell excitability, which is established by the synchronized activity of multiple diverse ion channels. K+ channels, the largest family of channels, control DSM excitability by maintaining the resting membrane potential and shaping the action potentials that cause the phasic contractions. Among the members of the voltage-gated K+ (Kv) channel superfamily, Kv type 7 (Kv7) channels — Kv7.1-Kv7.5 members encoded by KCNQ1-KCNQ5 genes — have been recently identified as functional regulators in various cell types including vascular, cardiac, and neuronal cells. Their regulatory roles in DSM, however, are just now emerging and remain to be elucidated. To address this gap, our research group has initiated the systematic investigation of human DSM Kv7 channels in collaboration with clinical urologists. In this comprehensive review, we summarize the current understanding of DSM Kv7 channels and highlight recent discoveries in the field. We describe Kv7 channel expression profiles at the mRNA and protein levels, and further elaborate on functional effects of Kv7 channel selective modulators on DSM excitability, contractility, and intracellular Ca2+ dynamics in animal species along with in vivo studies and the limited data on human DSM. Within each topic, we highlight the main observations, current gaps in knowledge, and most pressing questions and concepts in need of resolution. We emphasize the lack of systematic studies on human DSM Kv7 channels that are now actively ongoing in our laboratory.